Don't mess with the pancreas! A multicenter analysis of the management of low-grade pancreatic injuries. Issue 5 (November 2021) - Biffl, Walter L.; Ball, Chad G.; Moore, Ernest E.; Lees, Jason; Todd, S. Rob; Wydo, Salina; Privette, Alicia; Weaver, Jessica L.; Koenig, Samantha M.; Meagher, Ashley; Dultz, Linda; Udekwu, Pascal (Osi); et al.
Abstract : INTRODUCTION: Current guidelines recommend nonoperative management (NOM) of low-grade (American Association for the Surgery of Trauma-Organ Injury Scale Grade I–II) pancreatic injuries (LGPIs), and drainage rather than resection for those undergoing operative management, but they are based on low-quality evidence. The purpose of this study was to review the contemporary management and outcomes of LGPIs and identify risk factors for morbidity. METHODS: Multicenter retrospective review of diagnosis, management, and outcomes of adult pancreatic injuries from 2010 to 2018. The primary outcome was pancreas-related complications (PRCs). Predictors of PRCs were analyzed using multivariate logistic regression. RESULTS: Twenty-nine centers submitted data on 728 patients with LGPI (76% men; mean age, 38 years; 37% penetrating; 51% Grade I; median Injury Severity Score, 24). Among 24-hour survivors, definitive management was NOM in 31%, surgical drainage alone in 54%, resection in 10%, and pancreatic debridement or suturing in 5%. The incidence of PRCs was 21% overall and was 42% after resection, 26% after drainage, and 4% after NOM. On multivariate analysis, independent risk factors for PRC were other intra-abdominal injury (odds ratio [OR], 2.30; 95% confidence interval [95% CI], 1.16–15.28), low volume (OR, 2.88; 1.65, 5.06), and penetrating injury (OR, 3.42; 95% CI, 1.80–6.58). Resection was very close to significance (OR, 2.06; 95% CI, 0.97–4.34) ( p = 0.0584). CONCLUSION: The incidence of PRCs is significant after LGPIs. Patients who undergo pancreatic resection have PRC rates equivalent to patients resected for high-grade pancreatic injuries. Those who underwent surgical drainage had slightly lower PRC rate, but only 4% of those who underwent NOM had PRCs. In patients with LGPIs, resection should be avoided. The NOM strategy should be used whenever possible and studied prospectively, particularly in penetrating trauma. LEVEL OF EVIDENCE: Therapeutic Study, level IV.